Vascular Canals in Permanent Hyaline Cartilage: Development, Corrosion of Nonmineralized Cartilage Matrix, and Removal of Matrix Degradation Products. Issue 6 (2nd February 2017) - Gabner, Simone; Häusler, Gabriele; Böck, Peter
ABSTRACT: Core areas in voluminous pieces of permanent cartilage are metabolically supplied via vascular canals (VCs). We studied cartilage corrosion and removal of matrix degradation products during the development of VCs in nose and rib cartilage of piglets. Conventional staining methods were used for glycosaminoglycans, immunohistochemistry was performed to demonstrate collagens types I and II, laminin, Ki‐67, von Willebrand factor, VEGF, macrophage marker MAC387, S‐100 protein, MMPs ‐2, ‐9, ‐13, ‐14, and their inhibitors TIMP1 and TIMP2. VCs derived from connective tissue buds that bulged into cartilage matrix ("perichondrial papillae", PPs). Matrix was corroded at the tips of PPs or resulting VCs. Connective tissue stromata in PPs and VCs comprised an axial afferent blood vessel, peripherally located wide capillaries, fibroblasts, newly synthesized matrix, and residues of corroded cartilage matrix (collagen type II, acidic proteoglycans). Multinucleated chondroclasts were absent, and monocytes/macrophages were not seen outside the blood vessels. Vanishing acidity characterized areas of extracellular matrix degradation ("preresorptive layers"), from where the dismantled matrix components diffused out. Leached‐out material stained in an identical manner to intact cartilage matrix. It was detected in the stroma and inside capillaries and associated downstream veins. We conclude that the delicate VCs are excavated by endothelial sprouts and fibroblasts, whilst chondroclasts are specialized to remove high volumes of mineralized cartilage. VCs leading into permanent cartilage can be formed by corrosion or inclusion, but most VCs comprise segments that have developed in either of these ways. Anat Rec, 300:1067–1082, 2017. © 2016 Wiley Periodicals, Inc.